2017
DOI: 10.1097/nmd.0000000000000696
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences of Stressful Life Events, Coping Style, Symptom Severity, and Health-Related Quality of Life in Patients With Panic Disorder

Abstract: Although affective disorders have been known to have sex differences in the associated clinical characteristics and quality of life (QOL), sex differences among patients with panic disorder (PD) have remained relatively unexplored in Korea. We examined the sex differences in different types of stressful life events (SLEs), coping styles, symptom severity, and health-related QOL (HRQOL) in patients with PD. Data from 291 female and 254 male participants diagnosed with PD were analyzed using a structured clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
6
12
0
2
Order By: Relevance
“…Consistent with other studies, we have found that women with SMI present a statistically lower PCS of HRQOL than men with SMI [15][16][17]. For example, it has been reported that women with panic disorders have lower mean scores of HRQOL in the physical activity scale than men [41]. These results highlight that there are gender differences in general in our society and specifically, in people with mental health problems [42], both in psychiatric morbidity as well as in the pattern of behavior of different mental illnesses developed by men and women.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other studies, we have found that women with SMI present a statistically lower PCS of HRQOL than men with SMI [15][16][17]. For example, it has been reported that women with panic disorders have lower mean scores of HRQOL in the physical activity scale than men [41]. These results highlight that there are gender differences in general in our society and specifically, in people with mental health problems [42], both in psychiatric morbidity as well as in the pattern of behavior of different mental illnesses developed by men and women.…”
Section: Discussionsupporting
confidence: 92%
“…Correspondingly, this difference can be attributed to the difference in evasive coping score, which was higher in boys. In line with the present study, the results of a previous study showed that boys were more likely to use evasive coping behaviors such as self‐blame and substance abuse, compared to girls (Kim et al, 2017). Contrary to our findings, the results of other studies indicated that the use of evasive coping was greater in female subjects compared to male ones (Howerton & Van Gundy, 2009; Kim et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…et al., 2012). Some studies showed that females with PD have more illness burden of the health‐related quality of life, such as poor stress‐coping styles and missed work (Kim et al., 2017; Mclean et al., 2011). So we speculate that gender might mediate the association between PD and peripheral BDNF level; also, low peripheral BDNF level mignt play an essential role in the pathophysiological mechanisms of female PD patients (Molendijk.…”
Section: Discussionmentioning
confidence: 99%